2011
DOI: 10.1016/j.brainres.2011.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Are objects the same as groups? ERP correlates of spatial attentional guidance by irrelevant feature similarity

Abstract: It has been proposed that the most fundamental units of attentional selection are "objects" that are grouped according to Gestalt factors such as similarity or connectedness.Previous studies using event-related potentials (ERPs) have shown that object-based attention is associated with modulations of the visual-evoked N1 component, which reflects an early cortical mechanism that is shared with spatial attention. However, these studies only examined the case of perceptually continuous objects. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 61 publications
(88 reference statements)
4
20
4
1
Order By: Relevance
“…The N2 attention effect (300-350 ms) was shifted positively for connected objects in the easy condition. The present lack of N1 effect stands in contrast with our previous studies, which found attention-spreading effects in the N1 latency range (Kasai, 2010;Kasai et al, 2011;Kasai & Takeya, 2012;Takeya & Kasai, 2014). The general stimulus configurations and tasks in the current study were similar to those in the previous studies; the critical difference was that unfilled line stimuli, rather than geometric shapes with filled surfaces, were used.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…The N2 attention effect (300-350 ms) was shifted positively for connected objects in the easy condition. The present lack of N1 effect stands in contrast with our previous studies, which found attention-spreading effects in the N1 latency range (Kasai, 2010;Kasai et al, 2011;Kasai & Takeya, 2012;Takeya & Kasai, 2014). The general stimulus configurations and tasks in the current study were similar to those in the previous studies; the critical difference was that unfilled line stimuli, rather than geometric shapes with filled surfaces, were used.…”
Section: Discussioncontrasting
confidence: 55%
“…However, later ERP lateralization effects were also sensitive to grouping manipulations. The attention effects in the N2 latency range at around 300-400 ms for connected or similar stimuli were more positive than those for separated or dissimilar stimuli, respectively (Kasai, 2010;Kasai et al, 2011), and those in the P2 latency range (200-250 ms) were more positive for separated stimuli, although this result was observed only when another object was located between them (Kasai & Takeya, 2012).…”
Section: Introductioncontrasting
confidence: 37%
See 3 more Smart Citations